2014
DOI: 10.4103/0972-0707.144613
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of combined endodontic: periodontic lesion by sealing of palato-radicular groove using biodentine

Abstract: Introduction:Palatoradicular groove is a developmental anomaly which is predominantly found in maxillary lateral incisors. It provides a susceptible alcove for the progression of localised periodontal inflammation which can further cause pulpal involvement. This case report describes the successful treatment of a large periodontic – endodontic lesion usingnon surgical endodontic therapy and biodentine for the sealing of the palatoradicular groove.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…In patients with PPSE lesions with palatal radicular grooves, 42 45 the mean age was 26.5 years (minimum 19 and maximum 35). The mean age of patients with PPSE without radicular grooves was 48 years (minimum 40 and maximum 60), 10 ,– 16 ,– 35 ,– 39 – 46 considering patients with aggressive periodontitis 10 , 41 were not counted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with PPSE lesions with palatal radicular grooves, 42 45 the mean age was 26.5 years (minimum 19 and maximum 35). The mean age of patients with PPSE without radicular grooves was 48 years (minimum 40 and maximum 60), 10 ,– 16 ,– 35 ,– 39 – 46 considering patients with aggressive periodontitis 10 , 41 were not counted.…”
Section: Discussionmentioning
confidence: 99%
“…There were 18 teeth with PPSE (six molars 10,-16,-39-41 and 12 single-rooted teeth 35,[42][43][44][45][46] ) in the reviewed literature. Two molars were extracted without any treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Biodentine, a new calcium silicate-based material, is a bioactive dentine substitute with endodontic indications similar to those of MTA. [10111213] Biodentine powder mainly consists of tricalcium silicate, calcium carbonate, and zirconium oxide as the radiopacifier and its liquid contains a water reducing agent and calcium chloride as the setting accelerator. [14] A previous study showed that the teeth restored with biodentine maintained color stability, whereas those treated with wMTA exhibited discoloration.…”
Section: Introductionmentioning
confidence: 99%
“… 28 But Naik et al and Zucchelli et al have used biodentine and flowable composite, respectively. 29 30 Zucchelli et al also have demonstrated successful results by using papilla amplification flap and Emdogain (Institut Straumann, Waldenburg, Switzerland) which is unique of this case. 30 …”
Section: Discussionmentioning
confidence: 67%